Eletrodos de ouro modificados com complexos inorgânicos aplicados como sensores eletroquímicos para óxidos nítricos - Santos, Vanessa Nascimento dos (2012)
The aim of this work is to study the surface modification of gold electrode with the trans-[Ru(NH3)4(tina)(SO4)]+ (Au/trans-[Ru(NH3)4(tina)(SO4)]+) and trans-[Fe(cyclam)(NCS)2]+ (Au/trans-[Fe(cyclam)(NCS)2]+) complexes ion, emplyoing the electrodeposition and self-assembled monolayer techniques, respectively; and evaluate the potentiality of these modified electrodes as electrochemical sensors for detection and quantification of NO. Cyclic voltammetry and electrochemical quartz crystal microbalance results suggest that the deposition of trans-[Ru(NH3)4(tina)(SO4)]+ complex ion on the gold surface. Cyclic voltammetry and surface enhanced raman spectroscopy results confirm the modification of gold electrode surface by the trans-[Fe(cyclam)(NCS)2]+ complex ion. Peak current (Ip) observed in cyclic voltammograms for the oxidation of NO on the modified electrodes were higher than that observed for the unmodified gold electrode, and the modified electrode Au/trans-[Fe(cyclam)(NCS)2]+ showed the highest Ip for the oxidation of NO. The values of detection limit and quantification limit obtained for the electrode Au/trans-[Ru(NH3)4(tina)(SO4)]+ were 7.73 x 10-8 mol L-1 and 2.58 x 10-7 mol L-1, and for the electrode Au/trans-[Fe(cyclam)(NCS)2]+ were 5.15 x 10-8 mol L-1 and 1.72 x 10-7 mol L-1, respectively, being this values smaller by an order of magnitude as the same obtained for the unmodified gold electrode. Computational simulations suggest that the increase in Ip oxidation of NO on the electrode Au/trans-[Fe(cyclam)(NCS)2]+ is due to the interaction energy between molecules of NO and the complex trans-[Fe(cyclam)(NCS)2]+, adsorbed on the gold surface, to be stronger than the energy of interaction of NO with the gold surface. The dopamine and serotonin molecules and the nitrite ion interfere in electrochemical detection of NO and dopamine and serotonin showed greater interference in the detection of NO in relation to the nitrite ion. The electrode Au/trans-[Fe(cyclam)(NCS)2]+ showed the greatest stability when compared to the electrode Au/trans-[Ru(NH3)4(tina)(SO4)]+. The results obtained in this work showed the potentiality of modified electrodes as sensors for deteccion and quantification of NO, among which stands out the electrode Au/trans-[Fe(cyclam)(NCS)2]+ due to the further intensification of the signal current for the oxidation of NO and provided greater stability.